Apigenin-7-O-β-d-(6"-p-coumaroyl)-glucopyranoside reduces myocardial ischaemia/reperfusion injury in an experimental model via regulating the inflammation response - Wei Quan; Shanbo Ma; Yanrong Zhu; Qing Shao; Jixing Hou; Xiaoqiang Li (Taylor & Francis Group, 2020)
Context Traditionally, Clematis tangutica Korsh. (Ranunculaceae) is used as a Tibetan herb for treating indigestion and blood stasis in China. Recently, a flavonoid glycoside, apigenin-7-O-β-d-(6"-p-coumaroyl)-glucopyranoside (APG), was isolated from the whole plant of C. tangutica. Objective To investigate the cardioprotective effects of APG against myocardial ischaemia/reperfusion injury (MI/RI) and the possible mechanism. Materials and methods Animals were subjected to 30 min/3 h MI/RI model. At the end of reperfusion, infarct size (IS), histopathology, serum levels CK-MB, LDH, TNF-α, IL-6 and MPO activities were detected. Phospho-IκB-α, ICAM-1 and NF-κB were assessed in vivo. Neonatal rat cardiomyocytes were pre-treated with or without APG, followed by stimulation with 8 h/2 h oxygen and glucose deprived/reoxygenation (OGD/R) model. Cell viability, LDH and cardiomyocyte apoptosis were assessed. The expression levels of phospho-IκB-α and NF-κB were measured in vitro. Results Treatment with APG significantly reduced the following indicators in vivo (p < 0.05): (1) the IS (16.2%); (2) morphology score (1.67); (3) myocardial injury enzymes: CK-MB (26.2 ng/mL) and LDH (688 U/L); (4) pro-inflammatory cytokines: TNF-α (31.5 pg/mL) and IL-6 (163.8 pg/mL); (5) MPO activity (2.75 U/mg); (6) expression levels of phospho-IκB-α (0.47), NF-κB (2.87) and ICAM-1 (10.2). Moreover, treatment with APG also remarkably (p < 0.05) attenuated the following indicators in vitro: (1) LDH level (206 U/L); (2) cardiomyocyte apoptosis; (3) phospho-IκB-α (1.37) and NF-κB (2.50). Conclusions APG possesses protective effects against MI/RI injury in rats and OGD/R-induced injury in cardiomyocytes by suppressing translocation of NF-κB and reducing inflammatory response; consequently, APG is helpful for treatment of ischaemic heart disease.